Implementasi Kurikulum Berbasis Pesantren di MI Nurul Ulum Kretek Bantul - Siti Sholehah; Sukati Kati (Universitas Wahid Hasyim Semarang, 2020)
Abstract This reseach is started by researcher interest to MI Nurul Ulum Kretek Bantul as one of madrasah which apply curriculum based on national education system which integrated pesantren based–curriculum. This reseach aims to know about planning, implementing, monitoring, and evaluating those curriculums in MI Nurul Ulum. The type of this research is qualitative research. Subject of this research is the headmaster and some teachers. The technique of data analysis is using descriptive-analysis. Techniques and instrument of data collection is using observation, interview and documentation technique. To test the data validity, the researcher use triangulation technique. The finding of this research show that managements of pesantren based-curriculum in MI Nurul Ulum Kretek Bantul are as presented : 1. The planning of management pesantren based-curriculum already well running such as teaching preparation and other school programs, the preparation is carried out in early year school involving the headmaster and teacher, the foundation’s president, and commitees. 2. The implementation of curriculum management in MI Nurul Ulum is divided into 2 levels of studies : in school level is under headmaster leadership and class level is under teacher leadership. 3. The monitoring of curriculum management is conducted during the implementation of curriculum activities using observation and deliberation in class. 4. Evalution of curriculum management is conducted not only once in a year, but also every time when the obstacles occured, so the existing constraints do not accumulate.